2018
DOI: 10.1016/j.jgar.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Hospital adoption of antimicrobial stewardship programmes in Gulf Cooperation Council countries: A review of existing evidence

Abstract: Antimicrobial resistance is increasing at an alarming rate in the Gulf Cooperation Council (GCC) owing to the overuse and misuse of antimicrobials. Novel and rare multidrug-resistant strains can spread globally since the region is host to the largest expatriate population in the world as well as a pilgrimage destination for more than 4 million people annually. Adoption of antimicrobial stewardship programmes (ASPs) could improve the use of antimicrobials and reduce antimicrobial resistance in the region. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…The national ASP strategy of 2014 has so far been merely 'academic' and it has not been accompanied by any enforcement measures. Furthermore, the lack of national surveillance for antimicrobial use and AMR rates in Saudi Arabia [10,14] decreases motivation to reduce inappropriate antimicrobial use and marginalises the issue of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The national ASP strategy of 2014 has so far been merely 'academic' and it has not been accompanied by any enforcement measures. Furthermore, the lack of national surveillance for antimicrobial use and AMR rates in Saudi Arabia [10,14] decreases motivation to reduce inappropriate antimicrobial use and marginalises the issue of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…At a hospital level, evidence suggests the implementation of ASPs in some Saudi tertiary hospitals [7][8][9] and these ASPs are mainly led by infectious diseases (ID) consultants, with limited input from microbiologists and hospital pharmacists [7,8]. However, due to the shortage of ID consultants and microbiologists [2], these antimicrobial stewardship initiatives face sustainability challenges in tertiary care and are less likely to be implemented in secondary care where adoption of ASPs remains low [10]. Collaborations and the formation of ASP teams, including microbiologists, hospital pharmacists, physicians, nurses and infection control practitioners, could increase the capacity of hospitals to adopt ASPs and improve their implementation [11].…”
Section: Introductionmentioning
confidence: 99%
“…17 Although this recent review demonstrated that a few institutions in the GCC countries are implementing the core strategies of ASP, namely prospective audit with intervention and feedback and prior authorization of antimicrobials, it was evident from this review that the adoption of CDSS is still limited in this region. 17 Adoption of CDSS and computerized surveillance systems is imperative to further enhance the efficiency of ASPs, particularly in the setting of limited personnel support.…”
mentioning
confidence: 89%
“…A more recent review on the degree of adoption of ASPs in the GCC countries was conducted which highlighted the barriers for implementation including the lack of leadership support for ASPs, the lack of infectious diseases (ID) consultants and microbiologists, limited information technology (IT) infrastructure, and limited involvement of ID pharmacists in ASP . Although this recent review demonstrated that a few institutions in the GCC countries are implementing the core strategies of ASP, namely prospective audit with intervention and feedback and prior authorization of antimicrobials, it was evident from this review that the adoption of CDSS is still limited in this region . Adoption of CDSS and computerized surveillance systems is imperative to further enhance the efficiency of ASPs, particularly in the setting of limited personnel support.…”
mentioning
confidence: 99%
“…Despite these developments, literature on AMS programs in the UAE is sparse and mostly limited to published posters, government circulars, lectures or conference speeches. There is also an apparent weakness among existing work exploring the adoption of AMS programs in Abu Dhabi hospitals, with very poor reporting of outcomes and impacts . In response to this, the aims of the present study were to determine the status of adoption of AMS programs in the UAE and to identify the range of AMS program activities and practices implemented within hospitals in Abu Dhabi.…”
Section: Introductionmentioning
confidence: 99%